Lifestyle Behaviors Predict COVID-19 Severity: A Cross-Sectional Study - Yagmaee, Fateme; Taheri, Morteza; Irandoust, Kahdijeh; Mirmoezzi, Masoud (International journal of sport studies for health, 2023)
Background: The COVID-19 pandemic has put immense pressure on global health systems, especially developing countries with weaker health systems. Objectives: In the present study, we were looking to see if lifestyle behaviors could predict the severity and recovery duration of COVID-19. Methods: A total of 1 192 participants between the ages of 18 and 70 years participated voluntarily in a web-based survey. Food pattern and physical activity levels were respectively evaluated using the Food Frequency Questionnaire (FFQ) and the Rapid Assessment of Physical Activity (RAPA). The Pittsburgh Sleep Quality Index (PSQI) was also used to evaluate sleep disorders. Analysis of variance, chi-square test, and multinomial logistic regression were used to analyze the data. The significance level was P ≤ 0.05. Results: The findings suggested that patients with lower levels of physical activity, sleep disorders, and unhealthier dietary patterns were affected by more severe COVID-19 and longer recovery time (P ≤ 0.05). We found that physical activity and sleep quality predicted the severity of COVID-19, and physical activity and dietary patterns predicted the recovery time from COVID-19 (P ≤ 0.05). Conclusions: In conclusion, lifestyle behaviors, such as unhealthy diets, inactivity, and sleep quality disturbance, affect the severity and duration of COVID-19.